Sistem Monitoring Kualitas Udara Perpustakaan Sekolah Menggunakan Algoritma Fuzzy Logic Berbasis Internet of things - Syarifah Nurhafni Ahmad; LM. Fid Aksara; Asa Hari Wibowo (Jurnal Publikasi Teknik Informatika, 2025)
In the modern era, air quality has become a significant environmental concern, especially in indoor public facilities such as school libraries where students and staff spend considerable time. Poor indoor air quality can negatively affect health, concentration, and overall comfort, highlighting the need for a reliable monitoring solution. This study proposes the design and implementation of an Internet of Things (IoT)-based air quality monitoring system integrated with a Fuzzy Logic algorithm. The system utilizes a DHT-11 sensor to measure temperature and humidity and an MQ-135 sensor to detect harmful gases. Data are transmitted in real time using the WEMOS D1 Mini microcontroller and processed through the Mamdani Fuzzy Logic method, producing intuitive linguistic outputs such as “good,” “moderate,” and “poor.” Testing results demonstrate that the system can effectively monitor temperature, humidity, and toxic gas concentrations simultaneously with acceptable accuracy. The air quality assessments generated are simple to interpret and useful for decision-making, enabling schools to maintain a healthy and comfortable learning environment. Moreover, the system provides a low-cost and scalable solution that can be further expanded to other public facilities. Its combination of Internet of Things and Fuzzy Logic ensures adaptability, accuracy, and practicality for small-scale environmental monitoring applications in libraries.